Study the Relationship Physiology and Molecular Biology in Patients of Iraq Drug Use Parameters Acute Leukaemia (AL) - Ismail Ibrahim, Bushra; Hatem Abdulwahhab, Hayder (Clinical Medicine And Health Research Journal, 2023)
Study of paper is physiology use to analysis total in LDH is an intracellular enzyme whose activity is associated with cellular metabolism, WBCs count in blood to patients which makes it a marker of cell proliferation and cell injury and study with molecular biology of marker parameters use drug the presence of survivin in neoplastic cells contributes to tumor development and its high transcription has been reported as a predictor of poor prognosis in several hematological malignancies. However, despite being frequently present in ALs, the impact of survivin transcription in this type of hematologic malignancy remains undefined. Some studies report that survivin predicts an unfavorable clinical outcome in ALs, while others do not. In the present study, despite the small number of patients evaluated, the transcription of survivin at diagnosis did not seem to be related to a worse response to treatment or a worse prognosis. This is because, of the six patients who expressed survivin, three are in complete remission and, of the three who died, two were already considered to have an unfavorable prognosis regardless of survivin transcription, one due to advanced age and the presence of leukocytosis in the liver. Leukometry at diagnosis was another prognostic factor evaluated in this study. Patients diagnosed with AL may have elevated, normal, or decreased WBC counts at the time of diagnosis and, in general, counts greater than 30,000 WBCs/mm3 are considered to have a poor prognosis.